Martynas Mažvydas’ Forma Chrikʃtima: existing copies and their research history - Lemeškin, Ilja (Baltistica, 2025)
Martynas Mažvydas is known and celebrated as the founder of Lithuanian literature and the compiler of the first Lithuanian book. Naturally, this perspective gives special significance to the first Lithuanian book and its research, but this comes at the expense of his other books. Published in 1559, Forma Chrikʃtima is a mature author’s and experienced publisher’s individual and, in terms of genre, coherent work (the “fragmented” 1547 paleotype, which is heterogeneous in terms of genre and authorship, consists of different parts: a catechism and a hymnal), but it ended up alongside the unfortunate “third-row” books that do not receive much attention. In this respect, Forma Chrikʃtima repeats the fate of Pranciškus Skorina’s “Apostle” (1525), which even on this important anniversary remains in the shadow of the “Ruthenian Bible” (1517–1520) and the “Little Travel Book” (1522). Even the general public knows how many copies of M. Mažvydas’ catechism there are and where they are kept; with Forma Chrikʃtima, the situation is the opposite. The aim of this article is to provide a more detailed introduction to the second copy of the 1559 edition, which has been “ignored” by researchers until now, in the context of the history of research on Forma Chrikʃtima. This should encourage and facilitate the preparation of a critical edition of Forma Chrikʃtima for publication.